Sean Papile: capstone - Papile, Sean, artist (Colorado State University. Libraries, 2021)
The artist's statement: Whether I was aware of it or not, my work orbits around the ideas of the 20th century. Space age science fiction, midcentury design, pop art, nuclear fears, and the postwar Americana are all things I have great interest in. The work you see here is a reflection on the American mindset of the middle of the 20th century and concerns ideas that are as relevant now as they were then. Drawing Inspirations from 20th century artists Andy Warhol and Jasper Johns as well as others, these pieces invoke the language of repeated imagery as an aesthetic consequence of the 20th century and an expression of neutrality. The repeated image can tell us about our own perception of time, like a story board or how we perceive things that we see over and over again, as repetition is like a stone that dulls the human perception of imagery. Mass production has a similar effect on human psychology, distorting the value of what we see, buy, consume, or enjoy. These things are all what I consider when making these pieces, particularly the emotion of enjoyment and how deceptively simple that emotion can be. "Return to Earth" is a Narrative body of work that draws a similar inspiration from 20th century space age science fiction, and deepest a supposed return to a scorched post-nuclear earth years in the future. It invokes to use of cinematic language and storytelling through a still photographic medium. I've included it because like the other works in this portfolio, it is derived from the timeless visual language of the 20th century and is an expressed piece of my work and way of thinking.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making